1973
DOI: 10.2307/40166751
|View full text |Cite
|
Sign up to set email alerts
|

Behavior, Mimetic Songs and Song Dialects, and Relationships of the Parasitic Indigobirds (Vidua) of Africa

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Pressand American Ornithologists' Union are collaborating with JSTOR to digitize, preserve and extend access to Ornithological Monographs. http://www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
153
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(158 citation statements)
references
References 98 publications
(55 reference statements)
4
153
1
Order By: Relevance
“…For instance, some honeyguide (Friedmann 1955) and viduine (Payne 1973) male birds occupy call sites throughout the daytime and feed near these sites. In the case of indigobirds Vidua chalybeata (Payne & Payne 1977), distances from call-sites are mostly within 50 m of a village.…”
Section: ) Separation Of Breeding Area and Feeding Areamentioning
confidence: 99%
“…For instance, some honeyguide (Friedmann 1955) and viduine (Payne 1973) male birds occupy call sites throughout the daytime and feed near these sites. In the case of indigobirds Vidua chalybeata (Payne & Payne 1977), distances from call-sites are mostly within 50 m of a village.…”
Section: ) Separation Of Breeding Area and Feeding Areamentioning
confidence: 99%
“…Mimetic songs are easily identified in the field and provide direct evidence of the host species that reared each male indigobird. The identity of mimicry songs was confirmed by comparing sonograms generated in AVISOFT SAS LAB PRO (AviSoft Bioacoustics) with published sonograms of indigobirds and their hosts (Payne 1973;Payne & Payne 1994;Payne et al 2005). Female indigobirds do not sing and females of the three species at Tibati are morphologically similar; thus, host association and species identity of females can only be inferred through observations of social interactions with males.…”
Section: Methodsmentioning
confidence: 99%
“…The indigobird mating system has been described as a highly polygynous, dispersed lek (Payne & Payne 1977). Male indigobirds defend exclusive territories during the breeding season and devote most of their time to singing from a 'call site' at or near the top of a tree within the territory (Payne 1973). Territorial males were recorded using a Sony TCDM-5 cassette recorder and a Sennheiser ME-66 shotgun microphone.…”
Section: Introductionmentioning
confidence: 99%
“…Several ethologists and students of animal behavior have suggested that sexual imprinting might playa role in the evolution ofconspicuous characteristics, might generate sexual selection, or may increase the likelihood of speciation (Beach and Jaynes 1954;Mainardi 1964;Payne 1973;Immelmann 1974Immelmann , 1975ten Cate and Bateson 1988;Plotkin 1988;Gould and Gould 1989;ten Cate 1991). Central to these.…”
mentioning
confidence: 99%